Struktur koordinasi bahasa Aceh: kajian tipologi sintaksis - Tausya, Resi Syahrani; Effendi, Sultan Salman; Mulyadi, Mulyadi (Aksara: Jurnal Bahasa dan Sastra, 2023)
This study aims to describe the types of coordination in the Acehnese language at the clause level and determine whether the language can be classified as accusative or ergative. The research utilizes a qualitative descriptive approach to outline the pivot system in Acehnese and formulate applicable patterns using coordination structures as a combination of clauses in testing the pivot system. The findings of this study reveal four types of coordination in Acehnese: intransitive-intransitive, intransitive-transitive, transitive-intransitive, and transitive-transitive. Furthermore, the presence of syntactic ergativity properties can be observed in coordinated sentences in Acehnese, resulting from the elision of referential arguments when they function as patients and subjects. Additionally, Acehnese also exhibits syntactic accusative properties, where arguments from intransitive clauses are elided and co-referenced with agents. Keywords: Coordination Structure, Pivot, Aceh Language, Typology